Students’ Perception to Tutors’ Role In Problem Based Learning - Budiastuti, Veronika Ika; Soenarto, Sri Suparyati; Prihatiningsih, Titi Savitri; Kumara, Amitya (Faculty of Medicine Universitas Sebelas Maret, 2024)
Introduction: Studies show that student perception is an important determinant of student behaviour. Understanding the students’ perception is very useful for teachers to determine the appropriate learning approach for their students. The aim of this study is to find the effect of epistemological belief factor on students’ perception to tutors’ role in PBL tutorial discussion.Methods: This research is a qualitative research about student perception of tutor ‘s role in Problem Based Learning discussion. Respondents for this study consisted of 18 medical students that were divided into two groups based on their epistemological belief maturity level. Data were obtained through in-depth interviews with the respondents about their perception and expectations of how the tutor should works in accompanying students during the Problem Based Learning discussion. Data were analyzed using thematic content analysis.Results: The results show that students' perceptions of tutor‘s role are influenced by the differences of their problem-solving strategies. Students with simple knowledge perspective have the perception that the ideal tutor is a tutor who can make the discussions become structured and more orderly. Meanwhile, the group of students with mature epistemological beliefs argue that ideal tutors are the ones who can do critical analysis during Problem Based Learning discussion.Conclusion: The results of this study indicate that there is influence of epistemological belief maturity level to the students’ perception to tutors’ role in Problem Based Learning discussion.